Agricultural agglomeration or industrial integration: how does agricultural insurance bolster agricultural resilience in China? - Xie, Chen; Kuang, Yuan-pei; Wen, Hong-xing; Wu, Xiao-qing (Frontiers in Sustainable Food Systems, 2025)
Agricultural insurance has achieved rapid development in China, but its role in enhancing agricultural resilience remains unclear. This article aims to fill this research gap by investigating the impact and mechanism of agricultural insurance on agricultural resilience from the perspectives of agricultural agglomeration and industrial integration. The empirical results demonstrate that agricultural insurance exerts a significant and positive influence on the resilience of agriculture, which remains valid even after accounting for endogenous factors through the application of two IV sets. Further mechanism analysis reveals that agricultural insurance primarily boosts agricultural resilience by encouraging horizontal agricultural agglomeration rather than vertical industrial integration. Nevertheless, the influence of agricultural insurance on agricultural resilience differs among regions. Specifically, its effect on agricultural resilience is markedly more pronounced in the eastern and central regions compared to the less-developed western regions. Moreover, its effect on the agricultural resilience in the main grain-producing areas is obviously stronger than that in the main grain-selling area and those with a balance between production and marketing.